The Results of Pars Plana Vitrectomy in the Treatment of Intraocular Retinoblastoma: A Retrospective Study and Literature Review - Lu Li MD, PhD (SAGE Publishing, 2021)
Purpose: To assess the efficacy and safety of pars plana vitrectomy (PPV) as a treatment for intraocular retinoblastoma (RB) patients. Methods: Twenty-eight RB patients who had PPV were recruited in this retrospective case study, using the digital wide-angle retinal imaging device to record and assess disease condition. Results: The mean value of follow-up time was 79.4 months from diagnosis and 73.1 months from PPV. Up to the end of the follow-up time after PPV, the 5-year survival rate was 96.4%. Ultimately, 35.7% patients underwent enucleation of the eyeball. Among patients with salvaged eyes, 50% had no light perception vision. During the postoperative follow-up time, 14.3% of patients required no further antitumor treatment, and the remaining patients still need to continue to receive systemic or local antitumor treatment, such as chemotherapy, arterial interventional therapy, laser treatment, cryotherapy, and so on. The complication after PPV include cataracts (46.4%), iris adhesion (7.1%), emulsification of the silicone oil (17.9%), band degeneration of the cornea (10.7%), glaucoma (3.6%), and retinal neovascularization (3.6%). Conclusion: According to our observations, we recommend that the utmost care should be taken when considering PPV for the treatment of activated RB. When weighing the risk of tumor recurrence and metastasis, PPV is not suitable for routine treatment. It is necessary to fully grasp the operative indications and strictly observe operation specifications, which includes close postoperative follow-up.